An evaluation of the success rate of endodontic treatment done in U.P.C.D. year 1982-1983 - Fontanilla, Lerida Gem
This study serves to evaluate the success of endodontic treatment done in UPCD in the year 1982-1983, as well as to pinpoint the possible factors which lead to endodontic failures. Out of the 279 cases done in the said year, only 125 of these cases were recalled for evaluation. After carefully following the criteria for endodontic success and failures, it was found that the evaluated cases gave a rough value of 90% degree of success. Among all the recalled cases, it is interesting to note that the earliest endodontic treatment evaluated was done in 1954, the teeth having been restored to their normal function still remained to be integral part of the patient's oral cavity.